Ireland's international trade and transport connections - Martina Lawless; Edgar L. W. Morgenroth (The Economic and Social Research Institute (ESRI), 2017)
This paper looks at the transport patterns of Irish international trade. In particular, we examine how trade flows in weight differ from those measured by value and the implications that this has for transport mode and cost. In an environment of uncertainty relating to the impact of Brexit, the much larger share of the UK in total Irish export volumes (tonnages) compared to values signals possible significant impacts on transport and also on costs if increased customs procedures are introduced. We also look at the use of the UK as a land-bridge for Irish trade further afield, finding that a considerable percentage of Irish trade uses this transport option.
Keywords: F13; F14; F17; 330; Merchandise trade; transport; Brexit